Problématique du genre dans les situations de détresse : le cas des réfugiés en Afrique - Danièle Laliberté-Beringar (Refuge, 2002)
This article tries to take stock of male/female relationships in assembly areas related to wars, and especially in refugee camps. It also aims at showing how conflicts heighten inequalities between the sexes at every age level. The approach adopted has been to review scientific literature of the last decade, as well as the policies and programs of the UN High Commissioner for Refugees (UNHCR). The text is divided into several main parts: the place occupied by gender in research on refugees, in international aid, and refugee rights; a statistical overview; the transformation of the roles associated with gender; the difference in the impact of displacement depending on gender; and the vulnerability of refugee women and girls.